The impact of obesity, age, and gender on plasmatic levels of selected glycoprotein biomarkers and miRNA-499 in OSA patients - Kostlivý, Tomáš; Pešta, Martin; Windrichová, Jindra; Škopek, Petr; Klail, Pavel; Skálová, Alena; Gál, Břetislav; Kučera, Radek; Plicková, Krista; Šimánek, Václav; Slouka, David (Journal of applied biomedicine, 2024)
BACKGROUND: The current obstructive sleep apnea (OSA) diagnostic uses polysomnography or limited polygraphy and requires specialized personnel and technical equipment. Glycoprotein biomarkers and microRNAs are being explored as a possible new method for screening. We aimed to evaluate whether certain biomarkers and microRNA, previously identified as related to OSA, could be influenced by factors such as gender, age, and obesity level in patients with OSA. METHODS: In this retrospective analytical study, patients with moderate to severe OSA (n = 130) were compared with the control group. Serum levels of selected biomarkers and microRNA were taken from both groups. The group of OSA patients was then stratified by gender, obesity level, and age to see the possible influence of those variables on biomarker levels. RESULTS: Levels of all studied biomarkers - C-reactive protein (CRP), high-sensitivity troponin I (hsTnI), pentraxin-3 (PTX-3), and microRNA-499 were significantly higher in patients with OSA compared to the control group. In the OSA group only hsTnI showed a statistically significant relationship with gender. Levels of CRP and hsTnI showed a significant dependence on the level of obesity. Dependency on age was proven for hsTnI. CRP, PTX-3, and microRNA-499 did not have any statistically significant relationship with age. CONCLUSION: We found that serum levels of pentraxin-3 and microRNA-499 in patients with moderate to severe obstructive sleep apnoea are independent of gender, obesity, and age. CRP was affected by the level of obesity and hsTnI was influenced by all 3 variables. We consider these findings important for further research of OSA biomarkers.
Keywords: glykoproteiny; Male; MicroRNAs; biologické markery; retrospektivní studie; Obesity; Biomarkers; obstrukční spánková apnoe; sexuální faktory; mikro RNA; sérový amyloidový protein; obezita; Adult; Age Factors; C-reaktivní protein; Aged; dospělí; Sleep Apnea, Obstructive; mužské pohlaví; senioři; Glycoproteins; troponin I; lidé; ženské pohlaví; Humans; Sex Factors; Troponin I; věkové faktory; C-Reactive Protein; Retrospective Studies; Female; lidé středního věku; Serum Amyloid P-Component; Middle Aged